Peningkatan Partisipasi Masyarakat Dalam Pengelolaan Lingkungan di Desa Binaan Baru Kabupaten Barito Kuala - Fahri, Muhamad Agil; Budhi, Setia; Damayanti, Allisa; Widya, Widya; Laundari, Fransiska Triokta; Ramadhina, Aisyah; Andina, Farah; Nuriani, Nuriani (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2024)
Binaan Baru Village is one of the villages in Belawang Sub-district, Barito Kuala Regency. Binaan Baru Village is located on the banks of the Barito River, which is still part of the daily activities of the community. The waste issue in Binaan Baru Village is a very crucial problem that needs to be resolved because it has disrupted and affected the lives of the people of Binaan Baru Village. Because the waste problem in Binaan Baru Village did not receive full attention, the service team implemented the program “Building Waste Hazard Awareness Through Visualization of Waste Hazard in the Community of Binaan Baru Village” as a solution for the village. Through programs that are supported by living in the village for 35 days, the service team seeks to increase community participation and awareness of the importance of maintaining environmental cleanliness because it affects the social life of the people of Binaan Baru Village. In its realization, there are several programs implemented by carrying out activities including: 1) Handicrafts made from inorganic waste; 2) Appeal signs to protect the environment; 3) Mutual cooperation to clean the environment; 4) “Environmental Campaign” to raise public awareness in protecting the environment through films; 5) Socialization of waste sorting; 6) Provision of trash bins; 7) Joint discussion about the sustainability of the village environment. The result of this service is the action of gotong royong in cleaning the environment and making trash cans can attract the community and sympathize with environmental cleanliness. Socialization about waste sorting as well as teaching handicraft making made from inorganic waste. Through this program, the team hopes to encourage the community to increase their knowledge about the dangers of waste and be more concerned about waste management. So that a waste-free environment will be realized in the New Assisted Village.